2015
DOI: 10.1111/1365-2745.12379
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term C, N and P allocation to reproduction in Bornean tropical rain forests

Abstract: Summary1. Tropical rain forests in SE Asia are well known for the occurrence of supra-annual synchronous reproductive events, masting. Answering the question how trees allocate carbon (C), nitrogen (N) and phosphorus (P) to such irregular but gregarious reproduction requires a long-term observation. We conducted a 10-year continuous monitoring of litterfall in eight tropical rain forests, which differ significantly in P (and N) availability on Mount Kinabalu, Borneo. 2. Mean P concentration in reproductive org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
2
30
1
Order By: Relevance
“…Phosphorus (P) most frequently regulates tropical forest productivity (Vitousek 1984;Kitayama and Aiba 2002), suggesting that P may also limit tropical forest reproduction (see below for definition of the nutrient limitation to reproduction). In line with this hypothesis, Kitayama et al (2015) demonstrated a longterm trend in nine Bornean tropical rainforests for allocation of a disproportionately higher amount of P than C and N to reproduction; approximately 17% of P was allocated to reproduction, whereas C and N allocation was less than 10%. This finding indicated the significance of P for reproduction in Bornean tropical rainforests.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Phosphorus (P) most frequently regulates tropical forest productivity (Vitousek 1984;Kitayama and Aiba 2002), suggesting that P may also limit tropical forest reproduction (see below for definition of the nutrient limitation to reproduction). In line with this hypothesis, Kitayama et al (2015) demonstrated a longterm trend in nine Bornean tropical rainforests for allocation of a disproportionately higher amount of P than C and N to reproduction; approximately 17% of P was allocated to reproduction, whereas C and N allocation was less than 10%. This finding indicated the significance of P for reproduction in Bornean tropical rainforests.…”
Section: Introductionsupporting
confidence: 62%
“…We calculated nutrient-use efficiency of above-ground net primary production by dividing the total litterfall flux by the total nutrient flux (E). Nutrient-use efficiency can be considered an index of realized P deficiency (Vitousek 1984; Kitayama et al 2015). We compared the nutrient-use efficiency and E at the present study site with data for other tropical regions to understand the characteristics of the present study site, and how the masting event affected nutrient flux and ecosystem productivity.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The above-ground NPP (ANPP) was calculated as the sum of the above-ground biomass increment and the above-ground litterfall ( Table 1). The above-ground litterfall at each site was derived from the mean value of the 10-year observations between 1996 and 2006, as reported in Kitayama et al (2015).…”
Section: Estimation Of Above-ground Biomass and Net Primary Productivitymentioning
confidence: 99%
“…This nutrient demand reaches the same order of magnitude of annual N and P demand for annual litter production [3.0-3.7 kg P ha À1 year À1 from Fujii et al (2011) and Kitayama et al (2015)]. Phosphorus availability could therefore limit annual fruit production in dipterocarp forests in Southeast Asia.…”
mentioning
confidence: 95%